The first record of a species of Perlidae from Jiangsu Province, China: a new species of Neoperla (Plecoptera: Perlidae) - Chen, Zhi-Teng; Du, Yu-Zhou (Zootaxa, 2015)
A new species of Neoperla (Plecoptera, Perlidae), N. jiangsuensis Chen & Du from Jiangsu Province, China, is described and illustrated. Neoperla jiangsuensis is characterized by the aedeagal sac with two C-shaped rows of large stout spines laterally, a patch of small spines, and with an apical double ear-shaped membranous lobes. The new species is the first recorded species of Perlidae known from the eastern coastal province of Jiangsu, China.